Regional Differences of Women’s Online Shopping Behaviour in Kazakhstan: An In-Depth Analysis of the Factors - Kireyeva, Anel A.; Nurbatsin , Akan S.; Orynbet , Perizat Zh. (Economy of Regions, 2024)
Despite the growing popularity of online shopping, there is a lack of research on regional differences in consumer behaviour and preferences, particularly among women. The study aims to investigate the regional differences in women’s online shopping behaviour in Kazakhstan by conducting an in-depth analysis of the factors influencing female consumers. Using data from a survey of 400 women across different regions of Kazakhstan, logistic regression analysis was utilised to examine the relationship between online shopping frequency and several independent variables. The analysis found that the pandemic significantly affected online shopping behaviour in Kazakhstan, leading to decreased shopping frequency across all regions. Additionally, we found that women living in urban areas were significantly more likely to shop online frequently than those in rural areas, with an odds ratio of 0.504 (p = 0.014). The research also revealed notable differences in Internet penetration rates, with Karaganda, Pavlodar regions and Astana city having the highest rates among women (93.1 %, 93.0 %, and 94.5 %, respectively), while Atyrau and Kyzylorda regions had the lowest (80.7 % and 80.0 %). Therefore, it is recommended that policymakers should focus on expanding Internet infrastructure in remote regions by developing customised online marketplaces that meet the needs of urban areas like Almaty city. The findings of this study underscore the importance of considering regional differences in understanding the factors that drive online shopping behaviour in Kazakhstan. By investing in initiatives that promote e-commerce adoption and cater to consumers’ unique needs and preferences in different regions, policymakers can help foster a more inclusive and dynamic e-commerce ecosystem in Kazakhstan.